Effect of trichlorfon on some haematological and biochemical changes in Cyprinus carpio: The ameliorative effect of lycopene - Yonar, Serpil Mise; Yonar, M. Enis; Pala, Aysegul; Saglam, Naim; Sakin, Fatih (Elsevier, 2020)
Trichlorfon (TCF) is an antiparasitic agent used in aquaculture to treat external parasites and it belongs to the chemical class of organophosphates. This study was conducted to investigate the ameliorating effects of lycopene on TCF-induced toxicity in carp by evaluating haematological parameters and oxidant/antioxidant status. Fish were randomly divided into seven experimental groups. These groups were arranged as follows: control (no treatment) group, corn oil group, lycopene (10 mg kg(-1)) group, TCF-I (11 mg L-1) group, TCF-I (11 mg L-1) plus lycopene (10 mg kg(-1)) group, TCF-II (22 mg L-1) group and TCF-II (22 mg L-1) plus lycopene (10 mg kg(-1)) group. At the end of 14 days administration, blood and tissue (liver, kidney, and gill) samples were collected. Haematological changes [red blood cell (RBC) and white blood cell (WBC) count, haemoglobin (Hb) concentration, haematocrit (Ht) level, and erythrocyte indices: mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), and mean corpuscular haemoglobin concentration (MCHC)] were determined in the blood samples, while antioxidant parameters [(malondialdehyde (MDA) and reduced glutathione (GSH) levels and superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities] were evaluated in the liver, kidney and gill samples. The results demonstrated that all the haematological parameters were significantly decreased in the TCF-I and TCF-II groups when compared to the control group. Notable increases in the tissue MDA levels were observed in the TCF-treated groups. In contrast, significant decreases were observed in the tissue SOD, CAT and GSH-Px activities and GSH levels in the TCF-I and TCF-II groups. However, simultaneous treatment with lycopene provided a marked normalisation of the haematological and oxidant/antioxidant parameters compared with the TCF-I and TCF-II groups. The findings show that dietary lycopene supplementation might be helpful in abrogation of TCF toxicity by changing haematological conditions and antioxidant status in fish.
Keywords: Antioxidants; Fish; Haematology; Lycopene; Oxidative stress; Trichlorfon